PANDAS – a rare but severe disorder associated with streptococcal infections; Awareness is needed - Karin Frånlund; Charbél Talani (Acta Oto-Laryngologica Case Reports, 2023)
AbstractPANDAS is an acronym for ‘paediatric autoimmune neuropsychiatric disorders associated with streptococcal infections’ and is defined as a subgroup of PANS, ‘Paediatric acute-onset neuropsychiatric syndrome’. PANDAS is considered an autoimmune disease based on a streptococcal infection with a verified immune response. The onset is often dramatic, with symptoms of OCD developing within 24-48 h. Symptoms include both psychological symptoms and physical symptoms. Treatments of PANDAS must address both physical and psychiatric symptoms. Supplemental treatments for PANDAS include tonsillectomy to prevent further streptococcal infections. We present a case of PANDAS with the aim of raising awareness of its diagnosis. PANDAS is a rare condition with an impact on the patient’s quality of life; thus, awareness is needed. A multidisciplinary team is needed for diagnosis and treatment. Otorhinolaryngologists may play an important role in the well-being of these patients when performing tonsillectomy.